ALTERAÇÕES REPRODUTIVAS E GENOTOXICIDADE EM Sciades herzbergii (BLOCH, 1794) ASSOCIADAS À POLUIÇÃO AQUÁTICA NA COSTA MARANHENSE - NOLETO, Katherine Saldanha (2023)
Water pollution caused by chemical compounds, such as metals and PAH's (Polycyclic Aromatic Hydrocarbons), has been reported as the source of problems associated with the health and proper development of a wide variety of organisms. Considering the richness of aquatic ecosystems and the intense anthropization of the São José Bay region, in the State of Maranhão, Brazil, the objective of this research is to identify reproductive alterations and genotoxicity in Sciades herzbergii associated with water pollution in this region of the Maranhão coast. To do so, 68 specimens of S. herzbergii were collected in the estuary of São José Bay for biological analyses. In addition, water was collected for PAH analysis, and environmental variables of surface water were measured, such as pH, dissolved oxygen (mg L-1), temperature (°C) and salinity, using a multiparameter probe. Immediately after the collection, whole blood samples were obtained to perform the micronucleus test, aiming to identify erythrocyte nuclear alterations. Then the specimens were taken to the Laboratory of Technology Applied to Reproduction and Production of Nectonic Organisms - TARPON for the recording of biometric data. Fragments of gill and gonads were stained with Hematoxylin-Esosin (HE) and evaluated histologically by conventional microscopy. Muscle tissue samples were collected for the detection of Copper (Cu), Zinc (Zn), Iron (Fe), Magnesium (Mg), Aluminum (Al), Lead (Pb) and Cadmium (Cd). The metals Pb, Zn, Mg, Fe, Al in the muscle tissue were above the levels recommended by ANVISA (2013; 2021, 2005) and Decree N° 55871 of 1965. The analysis of PAHs revealed the presence of naphthalene and acenaphthene in the water samples. Histopathological tests showed testicular and ovarian melanomacrophages, oocyte follicular atresia and oocyte cytoplasmic retraction. In the gills, alterations of lamellar hyperplasia, displacement of lamellar epithelium, lamellar congestion and partial fusion of lamellae were detected. The genotoxic analyses indicated abnormal appearance of micronuclei, with mean micronucleus values very close to the values found by other authors in impacted areas. The results of Principal Component Analysis (PCA) indicated a relationship between Cu, Pb, Al, Fe and the melanomacrophage alterations, and between lamellar hyperplasia, Mg and Zn. Thus, it is concluded that S. herzbergii specimens collected in São José Bay-MA show reproductive and genotoxic alterations that might be associated with the contribution of contaminants (metals and PAHs) found in the water and tissues sampled.